Model Tests and Numerical Simulations of Liquefaction and Lateral Spreading 2019
DOI: 10.1007/978-3-030-22818-7_10
|View full text |Cite
|
Sign up to set email alerts
|

LEAP-2017: Comparison of the Type-B Numerical Simulations with Centrifuge Test Results

Abstract: This paper presents comparisons of 11 sets of Type-B numerical simulations with the results of a selected set of centrifuge tests conducted in the LEAP-2017 project. Time histories of accelerations, excess pore water pressures, and lateral displacement of the ground surface are compared to the results of nine centrifuge tests. A number of numerical simulations showed trends similar to those observed in the experiments. While achieving a close match to all measured responses (accelerations, pore pressures, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The key attributes of the DM04 formulation include the integration of a narrow conical yield surface, rotational (kinematic) hardening law, bounding surface, and dilatancy surface. These characteristics facilitate the simulation of the nonlinear mechanical behavior of granular soils subjected to both monotonic and cyclic loading conditions [30,31]. The general constitutive equation reads:…”
Section: Dafalias-manzari 2004 (Dm04) Modelmentioning
confidence: 99%
“…The key attributes of the DM04 formulation include the integration of a narrow conical yield surface, rotational (kinematic) hardening law, bounding surface, and dilatancy surface. These characteristics facilitate the simulation of the nonlinear mechanical behavior of granular soils subjected to both monotonic and cyclic loading conditions [30,31]. The general constitutive equation reads:…”
Section: Dafalias-manzari 2004 (Dm04) Modelmentioning
confidence: 99%
“…It was found that SANISAND model is capable of simulating the pore pressure generation in the free-field as observed in a recent centrifuge test. Recently, Manzari et al [141] compered 11 sets of Type-B numerical simulations with the results of a selected set of centrifuge tests conducted in the LEAP-2017 project. They obtained a good match trends in a number of numerical simulations with their experimental results.…”
Section: Two-and Three-dimensional Numerical Modellingmentioning
confidence: 99%
“…Eight sets of simulations provided results for the sensitivity analysis for relative densities of 50%, 65%, and 75%. During the Type-B simulations described by Manzari et al (2019b), the simulations by 5a-F2-Pm respected the prescribed densities but mistakenly used ρ max and ρ min reported by a different source, resulting in lower relative densities.…”
Section: D Comparisons Of Experimental Regression Surfacesmentioning
confidence: 99%
“…The 4-parameter and 6-parameter regression surfaces described above are compared to the Type-B predictions (Manzari et al 2019b) along with the results of the numerical sensitivity study in Fig. 11.5.…”
Section: -D Comparison Of Simulations To Experimental Regression Surmentioning
confidence: 99%